Perlindungan Hukum atas Martabat dan Privasi Perempuan dari Praktik Deepfake Pornografi - Nurhayati Chalil; Fathurrahim Fathurrahim (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
The phenomenon of deepfake pornography has caused serious violations of women’s dignity and privacy in the digital sphere. This study examines the normative gap within Indonesian law, which has yet to explicitly regulate deepfake practices, despite their severe impacts including psychological trauma, social stigma, and reputational damage for victims. The findings indicate that the existing legal framework remains fragmented and ineffective, thus failing to provide comprehensive protection. Consequently, this research recommends reconstructing legal protection based on human rights, gender justice, and digital ethics. It concludes that new technology-responsive regulations are urgently needed to safeguard women’s rights and ensure victim recovery.